In-situ neutron diffraction study of phase stability and equilibria in the Ti-rich part of the Ti–Al binary system. (May 2020) - Xu, Shuai; Reid, Mark; Liss, Klaus-Dieter; Xu, Yong; Zhang, Heng; He, Jianping; Lin, Junpin
Abstract: Three alloys with composition range of Ti-(25–35)Al (atomic %) were in-situ investigated using neutron diffraction to clarify the phase stability and equilibria in the Ti-rich part of the Ti–Al binary system. The phase transformation sequences of these three alloys were identified based on the neutron diffraction results and differential scanning calorimetry. No superstructure diffraction of β0 has been found in the neutron diffraction patterns. It is concluded that the β0 phase in the examined composition range is thermodynamically unstable. Based on the phase transformation sequences of these three alloys, combining the characters of congruent type relationship and peritectoid type relationship, the phase equilibria among β, α and α2 phases were confirmed as a peritectoid type, with two peritectoid reactions, i.e., β+α→α2 and β +α2 →α. Highlights: The phase stability and equilibria in Ti-rich Ti–Al system were in-situ investigated. The stability of β0 phase in Ti–Al binary system was denied. Two peritectoid reactions (β+α.→α2 and β+α2 →α) were identified in this work. The phase transformation temperature was identified by DSC. We redrew Ti rich Ti–Al phase diagram based on neutron diffraction and DSC results.